Far UV-C radiation: An emerging tool for pandemic control. Issue 6 (19th March 2023) - Blatchley, Ernest R.; Brenner, David J.; Claus, Holger; Cowan, Troy E.; Linden, Karl G.; Liu, Yijing; Mao, Ted; Park, Sung-Jin; Piper, Patrick J.; Simons, Richard M.; Sliney, David H.
Abstract: Far UV-C, informally defined as electromagnetic radiation with wavelengths between 200 and 230 nm, has characteristics that are well-suited to control of airborne pathogens. Specifically, Far UV-C has been shown to be highly effective for inactivation of airborne pathogens; yet this same radiation has minimal potential to cause damage to human skin and eye tissues. Critically, unlike UV-B, Far UV-C radiation does not substantially penetrate the dead cell layer of skin (stratum corneum) and does not reach germinative cells in the basal layer. Similarly, Far UV-C radiation does not substantially penetrate through corneal epithelium of the eye, thereby preventing exposure of germinative cells within the eye. The most common source of Far UV-C radiation is the krypton chloride excimer (KrCl*) lamp, which has a primary emission centered at 222 nm. Ozone production from KrCl* lamps is modest, such that control of indoor ozone from these systems can be accomplished easily using conventional ventilation systems. This set of characteristics offers the potential for Far UV-C devices to be used in occupied spaces, thereby allowing for improved effectiveness for inactivation of airborne pathogens, including those that are responsible for COVID-19. Graphical Abstract: UF0001